The Biogeochemistry of Electroactive Humic Substances and Its Connection to Iron Chemistry in the North East Atlantic and the Western Mediterranean Sea. Issue 8 (12th August 2018) - Dulaquais, Gabriel; Waeles, Matthieu; Gerringa, Loes J. A.; Middag, Rob; Rijkenberg, Micha J. A.; Riso, Ricardo
Abstract: We present the zonal distribution of electroactive humic‐like substances (eHS) along a section from Offshore Portugal in the North East Atlantic to the Sicily Channel in the Mediterranean Sea. The concentrations were normalized to Suwannee River Fulvic Acid and ranged from 11 μg/L to 81 μg/L. The vertical distributions were typical of those previously reported for dissolved organic carbon in the Mediterranean Sea. High eHS concentrations were measured in surface water and concentrations decreased with depth before increasing again toward benthic maxima measured at some stations. We estimate that eHS represented a relatively small fraction of the natural organic matter in the Mediterranean Sea (2–5%) but considering their important role in the complexation and the solubility of key trace elements (e.g., iron and copper), the eHS cycle could influence the entire biogeochemistry of these marine systems. We identified key processes controlling the concentration of eHS. While biologically mediated production was the major source of eHS, riverine and rain inputs as well as sediment release were also likely external sources. Low eHS concentrations at subsurface depths pointed to photodegradation as a possible sink of eHS, but degradation by heterotrophic bacteria seemed to be the main sink in the deep sea. Finally, we found a positive correlation between dissolved iron and eHS concentrations. Estimation of eHS contribution to iron binding ligand concentrations indicates the complexation of iron by eHS in the Mediterranean Sea. These observations suggest links between the cycles of eHS and iron in the Mediterranean Sea. Key Points: First zonal distribution of electroactive humic‐like substances (eHS) in the Mediterranean Sea In situ production in the euphotic layer and mineralization in the deep sea control eHS distribution Probable connection between eHS and iron Mediterranean biogeochemistry through an iron‐humic shuttle